TALE-Like Effectors Are an Ancestral Feature of the Ralstonia solanacearum Species Complex and Converge in DNA Targeting Specificity - Schandry, Niklas; de Lange, Orlando; Prior, Philippe; Lahaye, Thomas (Frontiers in Plant Science, 2016)
Ralstonia solanacearum, a species complex of bacterial plant pathogens divided into four monophyletic phylotypes, causes plant diseases in tropical climates around the world. Some strains exhibit a broad host range on solanaceous hosts, while others are highly host-specific as for example some banana-pathogenic strains. Previous studies showed that transcription activator-like (TAL) effectors from Ralstonia, termed RipTALs, are capable of activating reporter genes in planta, if these are preceded by a matching effector binding element (EBE). RipTALs target DNA via their central repeat domain, where one repeat pairs with one DNA-base of the given EBE. The repeat variable diresidue dictates base repeat specificity in a predictable fashion, known as the TALE code. In this work, we analyze RipTALs across all phylotypes of the Ralstonia solanacearum species complex. We find that RipTALs are prevalent in phylotypes I and IV but absent from most phylotype III and II strains (10/12, 8/14, 1/24 and 1/5 strains contained a RipTAL, respectively). RipTALs originating from strains of the same phylotype show high levels of sequence similarity (>98%) in the N-terminal and C-terminal regions, while RipTALs isolated from different phylotypes show 47-91% sequence similarity in those regions, giving rise to four RipTAL classes. We show that, despite sequence divergence, the base preference for guanine, mediated by the N-terminal region, is conserved across RipTALs of all classes. Using the number and order of repeats found in the central repeat domain, we functionally sub-classify RipTALs, introduce a new simple nomenclature, and predict matching EBEs for all seven distinct RipTALs identified. We experimentally study RipTAL EBEs and uncover that some RipTALs are able to target the EBEs of other RipTALs, referred to as cross-reactivity. In particular, RipTALs from strains with a broad host range on solanaceous hosts cross-react on each other’s EBEs. Investigation of sequence divergence between RipTAL repeats allows for a reconstruction of repeat array biogenesis, for example through slipped strand mispairing or gene conversion. Using these studies we show how RipTALs of broad host range strains evolved convergently towards a shared target sequence. Finally we discuss the differences between TALE-likes of plant pathogens in the context of disease